2019
DOI: 10.1192/bji.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in Malawi

Abstract: This is a reflective essay about the time I spent volunteering in mental healthcare in Malawi, prior to commencing my psychiatry training. The burden of illness I saw was enormous and the resources very limited; however, I describe some particular experiences where we were able to deliver excellent care, and which made me reflect about mental health services in low-income countries in general. Details of the patients discussed in this essay have been fully anonymised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Philippa Lilford describes, in vivid terms, her experiences as a junior psychiatrist in Malawi, which has but one mental hospital, in Zomba. 4 The asylum's origins lie in the local prison, where it was established in 1910; it has existed in its current form since 1953. Criticism of the in-patient system, in the context of Malawian society, was made by a senior government psychiatrist at the hospital nearly 30 years ago.…”
Section: Malawimentioning
confidence: 99%
“…Philippa Lilford describes, in vivid terms, her experiences as a junior psychiatrist in Malawi, which has but one mental hospital, in Zomba. 4 The asylum's origins lie in the local prison, where it was established in 1910; it has existed in its current form since 1953. Criticism of the in-patient system, in the context of Malawian society, was made by a senior government psychiatrist at the hospital nearly 30 years ago.…”
Section: Malawimentioning
confidence: 99%
“…To date, several facility-based studies in Malawi have reported a high burden of mental health disorders [ 27 , 28 ]. Nonetheless, most mental health conditions remain under diagnosed in the community due to limited availability of mental health services in primary care, and a lack of mental health funding and trained mental health professionals [ 29 ].…”
Section: Introductionmentioning
confidence: 99%